The Athenian Agora : museum guide - Gawlinski, Laura (The American School of Classical Studies at Athens, 2014)
Written for the general visitor, the Athenian Agora Museum Guide is a companion to the 2010 edition of the Athenian Agora Site Guide and leads the reader through all of the display spaces within the Stoa of Attalos in the Athenian Agora - the terrace, the ground-floor colonnade, and the newly opened upper story. The guide also discusses each case in the museum gallery chronologically, beginning with the prehistoric and continuing with the Geometric, Archaic, Classical, Hellenistic, Roman, and Byzantine periods. Hundreds of artifacts, ranging from common pottery to elite jewelry held in 81 case.